2021
DOI: 10.1002/stem.3328
|View full text |Cite
|
Sign up to set email alerts
|

ERG1 plays an essential role in rat cardiomyocyte fate decision by mediating AKT signaling

Abstract: ERG1, a potassium ion channel, is essential for cardiac action potential repolarization phase. However, the role of ERG1 for normal development of the heart is poorly understood. Using the rat embryonic stem cells (rESCs) model, we show that ERG1 is crucial in cardiomyocyte lineage commitment via interactions with Integrin β1. In the mesoderm phase of rESCs, the interaction of ERG1 with Integrin β1 can activate the AKT pathway by recruiting and phosphorylating PI3K p85 and focal adhesion kinase (FAK) to furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Notably, it was proposed that SKCa activation induces efficient cardiac differentiation of ESCs by activating the Ras-Mek1/2-ERK1/2 signal transduction pathway [118]. A recent study showed that the K + channel ERG1 is involved in the cardiac differentiation of rat ESCs by interacting with integrin β1 and thus activating the AKT pathway (Figure 4) [119]. The sources of intracellular Ca 2+ signals vary with the differentiation stage of PSCderived cardiomyocytes and embryos maintained ex vivo [121][122][123].…”
Section: Ion Channels and Transporters In Cardiac Differentiationmentioning
confidence: 99%
“…Notably, it was proposed that SKCa activation induces efficient cardiac differentiation of ESCs by activating the Ras-Mek1/2-ERK1/2 signal transduction pathway [118]. A recent study showed that the K + channel ERG1 is involved in the cardiac differentiation of rat ESCs by interacting with integrin β1 and thus activating the AKT pathway (Figure 4) [119]. The sources of intracellular Ca 2+ signals vary with the differentiation stage of PSCderived cardiomyocytes and embryos maintained ex vivo [121][122][123].…”
Section: Ion Channels and Transporters In Cardiac Differentiationmentioning
confidence: 99%
“…This adds to a growing body of work that highlights roles for KCNH2 that are unrelated to cardiac repolarization. Recent work in rat cells demonstrated that rERG1 complexes with integrin β1 to activate FAK signaling during cardiac differentiation and cardiac recovery following sepsis ( 49 , 50 ). hERG1 displays a similar role in cancer lines, where hERG1 promotes proliferation and metastasis ( 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular level, during cardiomyocyte differentiation, the maturation process of FAs plays an important role in activating different pathways and genes, such as integrin/FAK/PI3K-P85, which is activated by the interaction between laminins and early growth response protein 1 (ERG1), forming a complex with b1D integrin. The consecutive phosphorylation of FAK and PI3K-P85 activates AKT, inhibiting Wnt-GSK3b, which, in turn, upregulates β-catenin and GATA-4, necessary for cardiac differentiation [35][36][37][38].…”
Section: Focal Adhesions and Cardiac Cell Differentiationmentioning
confidence: 99%
“…Integrin/FAK/PI3K-P85 pathway FA's maturation process in cardiac differentiation. [35][36][37][38] FAK-Tyr397 phosphorylation Myocardial development, activate survival-promoting pathways. [45][46][47] Proteins Involved in FA Maturation Mint1/Veli/SAP97/CASK complex Structural and functional support to the sarcomere.…”
Section: Cardiomyocyte Myofibrillar Assemblymentioning
confidence: 99%